The Zaydi and Isma'ili Shiites in Al-Tabari’s History - Asmaa Mousa Abdelabbas, Rese.; Mohammed Allahverdi Zarghani, Prof. Dr.; Imdat Turan, Prof. Dr. (lark, 2025)
This study is significant for examining the history, doctrines, and historical events of the Zaydi and Isma'ili Shiite sects, as well as how Al-Tabari addressed these topics in his book History of the Prophets and Kings. The aim of the research is to extract and analyze all references related to the Zaydis and Isma'ilis within this major historical work. Al-Tabari’s book was chosen due to several key factors: its extensive collection of reports, its early and foundational nature, and its treatment of Shiism as a doctrine, including its figures and events. A notable reason for selecting this source is that Al-Tabari was not himself a Shiite, and therefore his coverage of Shiite topics reflects external, often non-Shiite perspectives, typically those of ruling authorities or other Islamic sects. In this context, the term “Shiites” refers specifically to the Twelve (Imami) Shiites, who follow Imam Ali, Hasan, Hussain, and the nine infallible Imams from the descendants of Hussain (peace be upon them). In contrast, the Zaydis diverged from the Imami school by following Zayd ibn Ali ibn Husayn and subsequent Zaydi Imams rather than the full line of Imams from Ahl al-Bayt. The Isma'ilis, on the other hand, followed Isma'il ibn Ja‘far after the death of Imam Ja‘far al-Sadiq, and did not recognize Imam Musa al-Kazim. Despite these doctrinal differences, both sects have had a significant impact on Islamic history, especially in the regions where their followers are concentrated. They consider themselves part of the Shiite tradition and believe in the legitimacy of their respective lines of Imamate. The objective of this research is to uncover and analyze all relevant material concerning the Zaydi and Isma'ili Shiites in Al-Tabari’s historical narrative.
Keywords: Shiites – Zaydis – Isma'ilis – Al-Tabari’s History.